A Cross-Level Examination of the Relationship of Strengths-Based Human Resource System With Employee Performance. (December 2022) - Ding, He; Yu, Enhai
Given the great significance of employees' strengths to employees' optimal functioning, strengths-based human resource (HR) system has gradually reaped HR researchers' attention. However, to date, there remains a lack of evidence supporting the effectiveness of strengths-based HR system. Therefore, this article aimed to bridge the gap in the literature by empirically testing the cross-level relationships between strengths-based HR system, employee strengths use, and supervisor-rated employee performance (i.e., task performance and innovative behavior). Data from 205 employees working in 56 organizations in China were collected at three points in time from different sources. The results of multilevel path analysis showed that strengths-based HR system has a positive relationship with employee strengths use, and employee strengths use is positively related to supervisor-rated employee task performance and innovative behavior. More importantly, strengths-based HR system had a positive relationship with employee task performance and innovative behavior via employee strengths use.